A 14‐3‐3 protein positively regulates rice salt tolerance by stabilizing phospholipase C1. (4th January 2023) - Wang, Ningna; Shi, Yiyuan; Jiang, Qun; Li, Huan; Fan, Wenxia; Feng, Yu; Li, Li; Liu, Bin; Lin, Feng; Jing, Wen; Zhang, Wenhua; Shen, Like
Abstract: The phosphatidylinositol‐specific phospholipase Cs (PI‐PLCs) catalyze the hydrolysis of phosphatidylinositols, which play crucial roles in signaling transduction during plant development and stress response. However, the regulation of PI‐PLC is still poorly understood. A previous study showed that a rice PI‐PLC, OsPLC1, was essential to rice salt tolerance. Here, we identified a 14‐3‐3 protein, OsGF14b, as an interaction partner of OsPLC1. Similar to OsPLC1, OsGF14b also positively regulates rice salt tolerance, and their interaction can be promoted by NaCl stress. OsGF14b also positively regulated the hydrolysis activity of OsPLC1, and is essential to NaCl‐induced activation of rice PI‐PLCs. We further discovered that OsPLC1 was degraded via ubiquitin‐proteasome pathway, and OsGF14b could inhibit the ubiquitination of OsPLC1 to protect OsPLC1 from degradation. Under salt stress, the OsPLC1 protein level in osgf14b was lower than the corresponding value of WT, whereas overexpression of OsGF14b results in a significant increase of OsPLC1 stability. Taken together, we propose that OsGF14b can interact with OsPLC1 and promote its activity and stability, thereby improving rice salt tolerance. This study provides novel insights into the important roles of 14‐3‐3 proteins in regulating protein stability and function in response to salt stress. Summary Statement: In Oryza sativa, a 14‐3‐3 protein, OsGF14b interacts with the phospholipase C1 (OsPLC1) and positively regulates rice salt tolerance. OsGF14b prevents OsPLC1 from degradation by inhibiting the ubiquitination of OsPLC1, contributing to maintenance of OsPLC1 stability under salt stress.